2021
DOI: 10.1021/acs.jafc.1c03533
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomics Analyses of Plantaricin Q7 Production by Lactobacillus plantarum Q7

Abstract: Plantaricin Q7 is a bacteriocin produced by Lactobacillus plantarum Q7 with food preservation potential. Low yield is one of the bottlenecks of the wide application of plantaricin Q7. Nontargeted metabolomics was performed to reveal the mechanism of plantaricin Q7 biosynthesis. The results showed that the composition and abundance of intracellular metabolites varied significantly at key time points of plantaricin Q7 synthesis. Differential metabolic pathways were purine metabolism; pyrimidine metabolism; alani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The function and utilization of L. plantarum have received much attention. At present, more and more bacteriocin-producing L. plantarum have been reported [ 15 , 16 ], but relevant studies were mainly focused on the isolation and purification, antibacterial mechanism and high-efficiency expression of bacteriocins [ 17 , 18 ]. There were few reports on the probiotic functions of bacteriocin-producing L. plantarum .…”
Section: Introductionmentioning
confidence: 99%
“…The function and utilization of L. plantarum have received much attention. At present, more and more bacteriocin-producing L. plantarum have been reported [ 15 , 16 ], but relevant studies were mainly focused on the isolation and purification, antibacterial mechanism and high-efficiency expression of bacteriocins [ 17 , 18 ]. There were few reports on the probiotic functions of bacteriocin-producing L. plantarum .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, L. plantarum could need l-Glu supplementation to metabolise it and enhance the bacteria growth 54 . Likewise, l-Glu could also be required to activate the secondary metabolism to produce postbiotic compounds such as GABA 55 or plantaricin 56 . Furthermore, l-Glu is usually supplemented directly into the fermentation media of L. plantarum strains due to this amino acid is the GABA precursor 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the upregulation of related genes and proteins in galactose metabolism, this could because the significant induction that occurs at low concentrations of glutamate and glutamine makes them the most economic strategy for enhancing plantaricin production in L. paraplantarum RX-8. Bu et al (2021b) reported that the plantaricin synthesis of L. plantarum Q7 was promoted by the exogenous addition of glutamate at 16 h, but plantaricin Q7 production was not stimulated by glutamate at 2, 6, and 12 h. Although S. cerevisiae could secrete different kinds of amino acids that are crucial to the survival of L. plantarum, the supplementing CDM35 medium with glutamine, threonine, phenylalanine, tryptophan, and serine, which were under the observed concentrations, had only a minimal impact on L. plantarum growth (Ponomarova et al, 2017). This is because the synergistic nature of multicomponent cross-feeding was challenging to characterize.…”
Section: Inducing E Ects Of Key Metabolites On Plantaricin Productionmentioning
confidence: 99%
“…Bacteriocins are proteins or peptides that display antibacterial activity against various spoilage and pathogenic bacteria (Bu et al, 2021b). Bacteriocins from lactic acid bacteria (LAB) are regarded as safe, natural antimicrobials for food biological preservatives (Bu et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%